Contemplating Interfaith Pastoral Counseling for The Spiritual Well-Being of Transwomen in The Seruni Community, Yogyakarta - Mutiara Andalas; Klara Gambacorta Larassati Suciari (Fakultas Teologi, Universitas Sanata Dharma, 2024)
The foundation of this study is the problem of social and spiritual orphanhood that transwomen in Yogyakarta's Seruni Community encounter as a result of social and spiritual exclusion. It is vital and urgent to contemplate interfaith pastoral counseling for the psychological and spiritual well-being of transwomen. The purpose of this qualitative study is to determine (1) how the transwoman community manages psychological and spiritual crises brought on by social and spiritual exclusion before getting interfaith pastoral counseling? (2) how does interfaith pastoral counseling contribute significantly to the psychological and spiritual well-being of transwomen? Transwomen going through spiritual and psychological orphanhood in Yogyakarta's Seruni Community served as the research subjects for this qualitative study. The study's findings indicate that (1) the transwoman community is marginalized in terms of both social and spiritual circles. Trans women pursue psychological and spiritual well-being through the communities they build before obtaining interfaith pastoral treatment. (2) Faith communities are contemplating interfaith pastoral counseling as a pastoral response to transwomen who are experiencing both psychological and spiritual orphanhood. Transwomen's psychological and spiritual well-being can be greatly enhanced by interfaith pastoral counseling, allowing them to fully flourish as persons and transform as believers.